RANKL and RANK: From Mammalian Physiology to Cancer Treatment. Issue 3 (March 2018) - Rao, Shuan; Cronin, Shane J.F.; Sigl, Verena; Penninger, Josef M.
Abstract : The tumor necrosis factor (TNF) receptor RANK (TNFRSF11A) and its ligand RANKL (TNFSF11) regulate osteoclast development and bone metabolism. They also control stem cell expansion and proliferation of mammary epithelial cells via the sex hormone progesterone. As such, RANKL and RANK have been implicated in the onset of hormone-induced breast cancer. Recently, RANK/RANKL were identified as crucial regulators for BRCA1 mutation-driven breast cancer. Current prevention strategies for BRCA1 mutation carriers are associated with wide-ranging risks; therefore, the search for alternative, non-invasive strategies is of paramount importance. We summarize here the functions of the RANKL/RANK pathway in mammalian physiology and focus on its recently uncovered role in breast cancer. We propose that anti-RANKL therapy should be pursued as a preventative strategy for breast cancer. Trends: RANK and RANKL are key molecules in bone physiology and regulate multiple aspects of the immune system. RANKL/RANK regulate the sex hormone progesterone, which promotes lactating mammary gland development during pregnancy, mammary stem cell expansion and proliferation, and drive the formation of hormone-induced breast cancer. RANKL/RANK control BRCA1 mutation-driven breast cancer, and its inhibition could be used as a preventative strategy.